Anatomic factors predict urinary continence in patient with anorectal malformation. Issue 5 (October 2020) - Fuchs, Molly E.; Halleran, Devin R.; Shin, Youn Ju; Sebastião, Yuri; Weaver, Laura; Ahmad, Hira; Booth, Kristina; Ching, Christina B.; Levitt, Marc A.; Wood, Richard J.; Dajusta, Daniel G.
Summary: It has been described that patients with more complex anorectal malformations (ARM), lower sacral ratios and spinal anomalies have poorer rates of fecal and urinary continence. While the ARM subtype has been shown to be an independent predictor of fecal continence, it is not well understood how each of these anatomic factors impact urinary continence. The purpose of this study was to identify anatomic factors associated with urinary continence in children born with ARM. We performed a retrospective review of a large prospectively collected database of children with ARM. Inclusion criteria included diagnosis of ARM, age >4 years, available lateral sacral ratio measurement and presence of spinal MRI. Any child with incomplete or absent continence data was excluded. Continence was defined as voiding per urethra volitionally, dry between voids and ≤1 urinary accident per week. Bivariable tests of association and log-binomial regression models were used to examine association between anatomic factors and urinary continence. A total of 434 patients were included in the study. 57.8% (n = 251) were male. Median age was 8.4 years (IQR 6.0–12.3). With regards to severity of ARM, 20.3% (n = 88) were complex, 23.3% (n = 101) were moderate and 56.5% (n = 245) were simple. Lateral sacral ratio included 11.1% (n = 48) that were <0.4, 36.2% (n = 157) 0.4–0.7 and 52.8% (n = 229) > 0.7. Spine status was found to be myelomeningocele in 4.4% (n = 19), low conus or tethered cord in 34.8% (n = 151) and normal or fatty filum in 60.8% (n = 264). Overall 62.2% were continent. ARM severity, lateral sacral ratio and spine status were each independent predictors of urinary continence on univariate and multivariable analysis. We conclude that in children born with ARM, the severity of ARM, lateral sacral ratio and spine status each independently predict urinary continence. These results allow us to better understand these complex patients and their ability to develop urinary continence. This is crucial in enabling proper patient and family counseling and thus, setting appropriate expectations. Image 1